The Effects of Introducing Mixed Payment Systems for Physicians: Experimental Evidence. (28th December 2015) - Brosig‐Koch, Jeannette; Hennig‐Schmidt, Heike; Kairies‐Schwarz, Nadja; Wiesen, Daniel
Abstract: Mixed payment systems have become a prominent alternative to paying physicians through fee‐for‐service and capitation. While theory shows mixed payment systems to be superior, causal effects on physicians' behavior when introducing mixed systems are not well understood empirically. We systematically analyze the influence of fee‐for‐service, capitation, and mixed payment systems on physicians' service provision. In a controlled laboratory setting, we implement an exogenous variation of the payment method. Medical and non‐medical students in the role of physicians in the lab ( N = 213) choose quantities of medical services affecting patients' health outside the lab. Behavioral data reveal significant overprovision of medical services under fee‐for‐service and significant underprovision under capitation, although less than predicted when assuming profit maximization. Introducing mixed payment systems significantly reduces deviations from patient‐optimal treatment. Although medical students tend to be more patient regarding, our results hold for both medical and non‐medical students. Responses to incentive systems can be explained by a behavioral model capturing individual altruism. In particular, we find support that altruism plays a role in service provision and can partially mitigate agency problems, but altruism is heterogeneous in the population. Copyright © 2015 John Wiley & Sons, Ltd.